The awareness towards zakat obligation among university students: A study in UniMAP - Nor Jannah, Ismail (2019)
Zakat is one of the important instruments in the economics of Muslims. Islam has laid down clear rules and regulations on zakat which is a religious obligation. The purpose of this study to examine the awareness towards zakat obligation among university students. The aim of this study is to investigate how independent variable which is contained of religiosity, knowledge, attitude, medium promotion, influenced the awareness towards zakat obligation. Besides, this study also trying to determine the relationship between all the variables mentioned. There are 365 respondents involved in this study while the test conducted are analysis descriptive correlation and regression. The findings indicated that there a positive and significant relationship between religiosity, knowledge, attitude, medium promotion and awareness towards zakat obligation. The multiple regression analysis also found that religiosity, knowledge, attitude, medium promotion is influenced and have its own impacts towards the awareness on zakat obligation among university students.